Membangun Ekonomi Pasca Covid 19 di Desa Sadah Tanah Merah Bangkalan melalui Pelatihan Pembuatan Keripik Kelapa - Junaidi, Junaidi; Ramdhan, Tri Wahyudi; Putera, Kholil Baita (LPPPM STAI Darul Hikmah Bangkalan, 2020)
The Covid 19 effect has made many people experience a decrease and even loss of income. One way that can be done to restore the economic activities of the community, especially in Sadah village, is by developing innovations from the local potential of the community. This service activity is carried out through the preparatory stage for program implementation by coordinating and conducting socialization to the community. Meanwhile, the program implementation process stage is carried out through workshops in each hamlet in Sadah Village. The output of this local government is a product that is brought by the Sadah Village community in processing coconut chips. It is hoped that the processed coconut chips will have more selling value so that they can restore the economy of the people of Sadah Village.